Anti-Hyperlipidemic Activity of Polyphenol-Rich Extract of Cochlospermum Planchonii Roots in Triton x-100 Induced Rats (Fountain Journal of Natural and Applied Sciences, 2020)
Cochlospermum planchonii is used for treatment of cardiovascular diseases in Nigeria and in some other African countries. This study investigated the anti-hyperlipidemic activity of polyphenol-rich extract of C. planchonii root in triton X-induced hyperlipidemic rats. Polyphenols were extracted from roots of C. planchonii with 80% aqueous methanol and acetone. Thirty female albino rats were randomized into six groups of five (5) rats each, Group I the non-hyperlipidemic control received saline only, group II the hyperlipidemic group received only saline, group III served as hyperlipidemic rats treated with 10 mg/kg b.w. atorvastatin while group(s) V-VII were hyperlipidemic rats treated with 25, 50 and 100 mg/kg b.w polyphenol-rich extract of C. Planchonii respectively. The effect of the administration of the extract on the serum lipid profile and hematological parameters was investigated. C. planchonii roots contained 47.7 ± 0.23 mg gallic acid equivalent / g dry extract and 49.14 ± 0.23 mg quercetin acid equivalent / g dry extract. Significant (p < 0.05) increase observed in serum total cholesterol, triacylglycerol and low-density lipoprotein with concomitant reduction in high-density lipoprotein concentration were mitigated by the polyphenol-rich extract. No significant changes were observed in the hematological indices of the hyperlipidemic rats at the doses investigated when compared to the control. The results indicated that polyphenol-rich extract of C. planchonii root exhibited anti-hyperlipidemic activity. Thus, it could be promoted as a recipe for protection against hyperlipidemia.Keywords: hyperlipidemia, Cochlospermum planchonii, polyphenol, lipid profile